Hay-Wells syndrome: Report of a rare disorder with dental management - Sonal B Dudhia; Bhavin B Dudhia; Jigna S Shah (Wolters Kluwer Medknow Publications, 2015)
Hay-Wells syndrome is a rare autosomal dominant disorder characterized by ankyloblepharon, ectodermal dysplasia, and cleft palate and/or cleft lip [ankyloblepharon-ectodermal dysplasia-clefting (AEC) syndrome]. Initially described by Hay and Wells in 1976, it is a rare form of ectodermal dysplasia with varying forms of expression featuring congenital abnormalities of the skin, hair, teeth, nails, and sweat glands. Recently, mutations in the p63 gene have been shown to be etiologic in the majority of cases of Hay-Wells syndrome. The present report describes the case of a 6-year-old boy who presented with ankyloblepharon, ectodermal dysplasia, and a cleft palate at birth, which are considered cardinal signs of this syndrome by most authors. The purpose of this article is to throw light on differentiating various ectodermal dysplasia syndromes associated with cleft palate and/or cleft lip and to highlight the importance of implementing multidisciplinary follow-up of patients with Hay-Wells syndrome.